Death-related Communication Between Healthcare Providers and Cancer Patients Receiving Palliative Care with Their Primary Caregivers - ทั้งไพศาล, ดารณี; Wongrujira, Monwipa; จันทร์รุ่งมณีกุล, อุณาโลม (Journal of Health Science of Thailand, 2022)
The objective of this research was to study the social construction of the meaning of death of healthcare providers, cancer patients receiving palliative care and their primary caregivers. This was a qualitative research based on case studies, using the methods of non-participatory observation and in-depth interviews with 16 key informants. The selection process began with purposively selecting 5 healthcare providers, comprising 1 doctor, 1 nurse, 1 radiologist, 1 government welfare officer, and 1 psychologist working at a hospital that cared for terminal cancer patients. Then, the snowball technique was used by asking the doctor to recommend 2 more doctors and 1 nurse who had expertise and was successful in providing palliative care; and they recommended 4 terminal cancer patients and 4 primary caregivers who had been evaluated by a psychologist and had passed the stress standard as recommended by the human research ethics committee. Data were analyzed through analytic induction. The results showed that the construction of the meaning of death of the doctor, the nurse, the radiologist, the government welfare officer, the psychologist, the doctors and nurse who were palliative care experts, the cancer patients themselves and their primary caregivers all varied with their different interpretations and perspectives, including their medical, religious, social, and economic outlooks. Each individual has an existing knowledge base that is a storehouse of accumulated social constructs. Even for the doctors, who had similar educational backgrounds and the same occupation, each had differing ideas and interpretations of the meaning of death and dying depending on their individual interests and knowledge banks. Learning, knowledge and experience were assembled, and the social construct of the meaning of death was transmitted through the communication process as each individual experienced various different environments and situations in the hospital throughout the course of care. The communication process naturally arose through social interaction in everyday life between healthcare personnel, cancer patients and primary caregivers as they negotiated death according to the knowledge base and social constructs that have been passed down from generation to generation, and that varies for different individuals depending on the time and place.